MICROELECTRONIC AUTOGENERATOR TEMPERATURE SENSORS - OSADCHUK, Iaroslav (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Microelectronic autogenerator temperature sensors based on transistor structures with differential negative resistance with primary parametric thermosensitive elements based on bipolar and field-effect transistors are proposed, moreover, primary parametric thermosensitive elements are active components of the circuits of parametric autogenerator temperature sensors, which greatly simplifies the design of the device. Based on the consideration of physical processes in primary parametric temperature-sensitive components and autogenerators of temperature sensors, mathematical models of autogenerator temperature sensors were developed, on the basis of which analytical expressions were obtained to determine the parametric dependences of sensitivity functions and transformation functions. It is shown that the main contribution to the conversion and sensitivity functions is made by a change in the ambient temperature, which causes a change in the equivalent capacitance and negative differential resistance of parametric autogenerator temperature sensors, which, accordingly, changes the output frequency of the device. The sensitivity of the sensor with a thermally sensitive bipolar transistor is from 11.25 kHz/°C to 21.5 kHz/°C, and the sensor with a thermally sensitive field-effect transistor is from 2.77 kHz /°C to 4.25 kHz/°C in the range of ambient temperature change 0 оС up to 100 оС. The obtained parametric dependences of the sensitivity and conversion functions show the possibility of easier calculation of the main characteristics of parametric autogenerator sensors, and also clearly demonstrate the influence of each component of parametric transducers and elements of parametric self-oscillating sensors on the output frequency of devices in comparison with the calculations of sensitivity and conversion functions from nonlinear equivalent circuits basis for solving the Kirchhoff equations.